2022
DOI: 10.1002/marc.202200490
|View full text |Cite
|
Sign up to set email alerts
|

NIR Photothermal‐Responsive Shape Memory Polyurethane with Protein‐Inspired Aggregated Chymotrypsin‐Sensitive Degradable Domains

Abstract: Biodegradable shape memory polymers are promising biomaterials for stents used in minimally invasive surgical procedures such as intestinal stents. Herein, a series of biodegradable shape memory polyurethanes (SMPUs) containing a novel phenylalanine‐derived chain extender (PHP) are synthesized. Inspired by the fact that the function of biomacromolecules such as proteins is rich and varied because of the multiple combinations of the amino acid in highly evolved biosystems, this study finds that the sequence dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…13). 43 The carbon black was introduced into the SMPU to provide photothermal-induced shape recovery properties to the PU. In order to enhance the compatibility between SMPU and carbon black, the surface of carbon black was oxidized to increase the carboxyl content, which was conducive to the dispersion of carbon black in SMPU solution in the DMF and SMPU membrane matrix.…”
Section: Other Carbon-based Photothermal Agent Containing Smpumentioning
confidence: 99%
See 2 more Smart Citations
“…13). 43 The carbon black was introduced into the SMPU to provide photothermal-induced shape recovery properties to the PU. In order to enhance the compatibility between SMPU and carbon black, the surface of carbon black was oxidized to increase the carboxyl content, which was conducive to the dispersion of carbon black in SMPU solution in the DMF and SMPU membrane matrix.…”
Section: Other Carbon-based Photothermal Agent Containing Smpumentioning
confidence: 99%
“…81 Herein, Yang et al (2022) reported a biodegradable PU with NIR light-induced photothermal responsive shape memory property, as a potential implantable material for intestinal stents. 43 A novel chain extender phenylalanine (PHP) derivative with two chymotrypsin cleavage sites was first synthesized. 82 The SMPU was prepared by reacting HDI, PCL-4000 diol, PHP chain extender, and oxidized carbon black (OCB) as photothermal agent (Fig.…”
Section: Other Carbon-based Photothermal Agent Containing Smpumentioning
confidence: 99%
See 1 more Smart Citation
“…2 Due to the good biocompatibility and designability of their chemical structure, shape memory polyurethanes (SMPUs) have potential applications in biomedical devices, especially self-expanding vascular stents. [3][4][5][6][7][8] However, vascular stents made of SMPs or SMPUs are generally confronted with a significant reduction in radial support after shape recovery and are even insufficient to support the narrow parts. 9 When used in vivo, the switching phases of SMPUs are always stiff below the transition temperature (T trans ) but they become flexible to facilitate the shape recovery accompanied by the reduction of stiffness when heated to reach the T trans , 10 and the modulus is dramatically declined in a 37 1C aqueous environment due to the strong plasticization of water.…”
Section: Introductionmentioning
confidence: 99%